KONSEKUENSI HUKUM TERHADAP VAKSINASI DALAM PERPEKTIF HAM - Luhukay, Roni Sulistyanto (Lex Journal: Kajian Hukum & Keadilan, 2021)
The increase in Covid patients in Indonesia has made the Indonesian government work quickly in increasing the community's immunity by vaccinating as a form of government responsibility in providing health insurance. The government's responsibility is not only limited to giving gifts, but the government is responsible for post-work follow-up events (KIPI), namely medical events suspected of involving works of art. The government remains responsible for patients who experience health problems. In the implementation in Jakarta, there are considerations between regulations that require vaccines with punitive consequences and human rights arrangements that guarantee the right to health, which is a personal right. by giving individuals the right to determine health services for themselves. For this reason, it is a right that comes from an idea in constitutionalism to limit the power of power in such a way, so that the exercise of power is not arbitrary and thus it is hoped that the rights of citizens will be more protected, because that right has arisen before the constitution was created. alone. Keywords: Information, Law, Vaccination, Human Rights.